A direct and accurate adaptive semi-Lagrangian scheme for the Vlasov-Poisson equation - Campos Pinto, Martin (Zielona Góra: Uniwersytet Zielonogórski)
This article aims at giving a simplified presentation of a new adaptive semi-Lagrangian scheme for solving the (1 + 1)-dimensional Vlasov-Poisson system, which was developed in 2005 with Michel Mehrenberger and first described in (Campos Pinto and Mehrenberger, 2007). The main steps of the analysis are also given, which yield the first error estimate for an adaptive scheme in the context of the Vlasov equation.
Keywords: fully adaptive scheme; semi-Lagrangian method; Vlasov-Poisson system; error estimates; convergence rates; optimal transport of adaptive multiscale meshes